Diffusion model of gas hydrate dissociation into ice and gas: Simulation of the self-preservation effect. (November 2016) - Vlasov, Valeriy A.
Highlights: A kinetic model of gas hydrate dissociation into ice and gas is proposed. The intrinsic kinetics of gas hydrate dissociation was taken into account. The gas hydrate self-preservation effect is simulated. The diffusion coefficient of methane in ice is estimated. The anomalous preservation thermal regime of gas hydrates is explained. Abstract: The diffusion model of gas hydrate dissociation into ice and gas is presented. This model takes into account the possible porous structure of the formed layer of ice as well as the intrinsic kinetics of the process of gas hydrate dissociation into ice and gas. Specifically, the problem of the dissociation of a spherical gas hydrate particle into ice and gas was considered. In the framework of a quasi-stationary approximation, a simplified solution to this problem was obtained. From the comparison between the calculated data obtained in the framework of a quasi-stationary approximation and the available experimental data, the parameters of the developed model responsible for the kinetics of methane hydrate dissociation into ice and gas were estimated. In the framework of the developed diffusion model, an explanation for the anomalous preservation thermal regime of gas hydrates is given. From this explanation it follows that for some hydrate-forming gases such a regime may not occur.